A Preliminary Study of a Graphene Fractal Sierpinski Antenna. Issue 1 (May 2020) - Boretti, Alberto; Rosa, Lorenzo; Blackledge, Jonathan; Castelletto, Stefania
Abstract: We provide a preliminary study of a Graphene fractal antenna operating at THz frequencies with the opportunity to modulate the emission. There are many advantages of the fractal design, namely multiband/wideband ability, and, a smaller, lighter and simpler configuration for higher gain, that can benefit from the coupling with Graphene, the thinnest and strongest of materials exhibiting very high electrical conductivity and tunability. This paper proposes a conceptual background for the study and presents some preliminary results on the electromagnetic emission simulations undertaken.